Percepção dos estudantes de medicina acerca da especialidade medicina de família e comunidade. - PINTO, Larissa Bordalo de Figueirêdo (2020)
INTRODUCTION: Primary Health Care is defined through its attributes, namely first contact access, longitudinality, comprehensive care, coordination of care, family and community orientation and cultural competence with great transformative potential for graduation, but there is still little data in Brazil that indicate students' perception of Family and Community Medicine, especially in municipalities and services with primary care not active. This study presents principles that govern the exercise of this specialty and its fields of activity, as well as the applicability during graduation in Medicine. OBJECTIVE: To identify the knowledge about the performance of the Family Health Strategy (ESF) as well as the influencing factors in the choice of family and community medicine (CFM) in the research sample. METHODOLOGY: This is a cross-sectional study of qualitative, exploratory approach, involving 62 (sixty-two) undergraduates from the fifth and sixth year of the medical course in a Public Institution and another Private institution in the city of São Luís - MA, during the months of January to March 2020. A sociodemographic questionnaire and a script for semi-structured interviews were used to collect data, identifying professional aspirations as a way of analyzing the factors that influence the choice of this Specialty. RESULTS: The majority are women (60.3%), single (52%), without children (97.2%), white (54%), from the capital São Luís - MA (51.3%), average family income of 10 minimum wages (32.25%), most without medical relatives (62.1%) and with 70% of Focal Specialists, distributed in: Radiology, Clinical Medicine, Dermatology and Psychiatry. The career of a Family and Community Doctor was considered "regular" (42.8%), taking into account the factors that motivated the choice for this Specialty that are the existence of a career plan with good salaries, the good physical structure in the PHC Unit, the daily coexistence with teachers specialized in CFM, the opportunity to solve various health problems and , finally, contact with the Community, humanization and equity. Slightly more than half of the undergraduate students participating in the study (51.6%) was undecided about the following Specialty and none of the students were willing to specialize in CFM. CONCLUSIONS: The study concluded that factors related to the context of graduation (the experience with preceptors specialists in Family and Community Medicine), as well as the improvement in the resolution of the ESF, both related to the physical structure, as valorization and Plans of Positions and Salaries would be the reasons that would effectively contribute to the growth of primary care, sustainability of the Health System and choice of Family and Community Medicine as a Medical Specialty to medical undergraduates in the city of São Luís - Ma.